SPONTANEOUS OVARIAN HYPERSTIMULATION SYNDROME (CLINICAL CASE) - Лариса Егоровна Фетищева; Любовь Никитична Петрич; Светлана Ивановна Елгина; Елена Владимировна Рудаева; Кира Борисовна Мозес (Медицина в Кузбассе)
Ectopic pregnancy, unfortunately, is a formidable diagnosis for the patient, as it is characterized by the development of massive bleeding, which can lead not only to the loss of reproductive function, but also to the death of the patient. The frequency of rare forms of ectopic pregnancy reaches 5-8.3% of all ectopic pregnancies. Therefore, early diagnosis of such forms of pregnancy is so relevant. The case of a rare form of ectopic ovarian pregnancy presented in the article is undoubtedly of clinical interest for obstetricians and gynecologists.